2023
DOI: 10.1038/s41598-023-30339-y
|View full text |Cite
|
Sign up to set email alerts
|

Euryhaline fish larvae ingest more microplastic particles in seawater than in freshwater

Abstract: Microplastic (MP) pollution is a major concern in aquatic environments. Many studies have detected MPs in fishes; however, little is known about differences of microplastic uptake by fish in freshwater (FW) and those in seawater (SW), although physiological conditions of fish differ significantly in the two media. In this study, we exposed larvae (21 days post-hatching) of Oryzias javanicus (euryhaline SW) and Oryzias latipes (euryhaline FW), to 1-µm polystyrene microspheres in SW and FW for 1, 3, or 7 days, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…Thus, MP particles exposed to larvae in this research were considerably minuscule to be confused as food. Consequently, we believe that the primary factor influencing MP ingestion in Oryzias latipes larvae in this study is water drinking for the osmoregulatory process, as reported in our previous study [14]. An earlier study by Kaneko and Hasegawa stated that water drinking of O. latipes larvae in freshwater was proven, although the rate is lower than that in seawater [17].…”
Section: Microplastic Ingestion and Possible Uptake Routes In Fish La...supporting
confidence: 70%
See 1 more Smart Citation
“…Thus, MP particles exposed to larvae in this research were considerably minuscule to be confused as food. Consequently, we believe that the primary factor influencing MP ingestion in Oryzias latipes larvae in this study is water drinking for the osmoregulatory process, as reported in our previous study [14]. An earlier study by Kaneko and Hasegawa stated that water drinking of O. latipes larvae in freshwater was proven, although the rate is lower than that in seawater [17].…”
Section: Microplastic Ingestion and Possible Uptake Routes In Fish La...supporting
confidence: 70%
“…MP extraction and counting were performed as described in the previous report [14], with several modifications. For MP extraction, larvae samples from the exposure phase (Day 1 and 3) and elimination phase (Days 4 and 6) were evenly crushed in 20 mM HEPES solution.…”
Section: Microplastic Extraction and Automatic Countingmentioning
confidence: 99%